The Role of Artificial Intelligence for Medical Professionals in Indonesia: A Systematic Literature Review - Sigit Ahmadi; Nur Wening (Al-Makki Publisher, 2025)
The development of Artificial Intelligence (AI) technology has brought significant transformation to the global healthcare system, including in Indonesia. This study aims to systematically examine the implementation and impact of AI on the performance of medical personnel in Indonesia through a systematic literature review approach. The research method follows the PRISMA protocol by analyzing scientific publications from 2019 to 2024 obtained from the Google Scholar, PubMed, ScienceDirect, and Indonesian Medical Journal databases. The results indicate that the application of AI has contributed positively to improving diagnostic accuracy (87.5%), healthcare service efficiency (82.3%), and clinical decision-making quality (85.2%). Nevertheless, this study also highlights significant challenges in the implementation of AI, such as limited digital infrastructure (65.4%), inadequate competence among health human resources (58.7%), concerns over data privacy and security, and the lack of comprehensive regulatory frameworks (52.3%), all of which hinder optimal integration. This study provides a scientific foundation for policymakers to develop regulations that support AI adaptation in healthcare while safeguarding ethical standards and patient safety. Additionally, the research offers practical insights for future studies to focus on overcoming technical, educational, and legal barriers, ensuring that AI integration advances equitable and sustainable healthcare services in Indonesia.